Pemberdayaan Investor Saham Pemula dengan Melakukan Investasi Saham Bermodalkan Sampah - Mirza Hedismarlina Yuneline (jurnal ABDIMAS Indonesia, 2023)
Based on data from the Ministry of Environment, the Indonesian population produces around 2.5 liters of waste per day or 625 million liters of the total population. Waste produced in households includes organic waste, inorganic waste and B3 waste (Toxic and Hazardous Materials). The problem in the city of Bandung is the lack of awareness among the public. People still throw away waste without separating it between organic and inorganic. By sorting waste, waste can be reused directly by making crafts from used goods and reused indirectly by selling used goods to scavengers, junkyards or waste banks. This waste-related problem is then elaborated on the capital requirements that novice investors usually face. The solution to the problem is in the form of awareness regarding waste sorting, then processing the waste into products that have selling value. Then the proceeds from the product selling can be used for investment by topping up the customer funds account) which can then be used to buy stock in the capital market.